Appropriate food packa g i n g solutions for developing countries - Nerlita M. Manalili (FOOD AND AGRICULTURE ORGANIZATION OF THE UNITED, 2011)
The study assesses the state of packaging and packaging technologies in developing countries, with the challenge of global food losses and the potential for agri-food systems as the backdrop. The purpose of the exercise is to identify packaging solutions in developing countries, within the limits of prevailing levels of development and conditions, and in an attempt to make better use of the locally available packaging materials. This is done within the framework of developing countries’ role as major supplier to the global food system and, consequently, as contributor to the search for global food loss solutions. Highlights of the study are as follows: On the status of packaging industry sectors in developing countries The food packaging industry sector of developing countries derives its strength from the large volume of agricultural production, the steady growth in food commodities and the continually increasing food demand fuelled by rising incomes. Industry limitations that beset the packaging sector across developing regions include limited packaging solutions to meet international market requirements, and the small size of the domestic demand for packaging materials that consequently leads to low investment by the packaging industry. This, in turn, limits developing countries’ ability to enhance product quality to meet standards of increasingly discriminating consumers, both in domestic and international markets. On the packaging sector’s opportunities and potential in developing countries As many products exported to developed countries are already processed at point of origin, the demand for these to be packaged in retail friendly form is on the rise and this is an opportunity for the developing economies to take advantage of. Of the three subsectors of the packaging industry (manufacturing, machinery and service), there appears greatest potential to develop package manufacturing in developing countries, given the tendency to process nearer to the production source and the availability of paper and paper board packaging materials. As to packaging machinery, creativity in coming up with locally designed equipment suited to local needs and conditions will help propel packaging industry development. While this strategy is in its infancy, developing countries will mainly have to rely on second-hand machines with their lower cost offsetting the cost of maintenance. This is because of the prohibitive cost of brand new ones. Developing the packaging service provision subsector, specifically pre-packing of food products for export, and outsourcing the packaging of food products to specialized companies, will provide a much-needed boost to the packaging industry in developing countries. They will not only lend affordability of packages and packing but will likewise enhance handling and distribution efficiencies to exporters, specifically to SMEs. On addressing the low investment in packaging industries in developing countries Initiatives towards growth of packaging industries in developing countries may come either from improving traditional technologies or importing new ones. However, more relevant than the appropriateness and balance of the selected mix of strategies, the success of these initiatives will be contingent on a country’s enabling environment, both economic and political. As packaging materials are in short supply in developing countries, relaxing packaging regulations without sacrificing food safety considerations may assist the industry to develop. An example is allowing the use of recycled packaging materials when they pose no problem of contamination (i.e. for use with dried foods). Such relaxation of packaging standards will help increase supply of packaging materials while at the same time addressing food loss concerns. While prospects are bright for the growth of the packaging industry sector, it will be for the good of the industry, the stakeholders comprising it and society at large, if focused packaging solutions, taking into account sustainability concerns, are provided to meet the sector’s needs. This will not only bring about cost savings but will likewise be good for the environment.